Narciclasine inhibits vaccinia virus infection by activating the RhoA signaling pathway - Ting Xu; Zhengyang Pan; Xue Li; Mengyang Zhao; Zichen Li; Leiliang Zhang (Biosafety and Health)
In 2022, a sharp rise in global cases of mpox virus (MPXV) led the World Health Organization (WHO) to declare it a public health emergency of international concern. However, progress in developing drugs targeting MPXV has been slow. Here, we investigate the natural alkaloid narciclasine as a potential inhibitor of poxviruses. Our investigation demonstrates that narciclasine at 40 nmol/L (nM) to 160 nM dosages effectively blocks vaccinia virus (VACV), a representative poxvirus. Specifically, narciclasine disrupts the production of extracellular enveloped virus (EEV), which is crucial for viral spread. Narciclasine’s antiviral impact is probably attributed to its activation of the RhoA signaling pathway. This study highlights narciclasine’s potential as a promising new therapeutic candidate against poxviruses, offering prospects for its development into a potent antiviral agent that is essential for combating emerging poxvirus outbreaks.